A granger - causality analysis on the public deficit - money supply relationship: some evidence for Greece - Αλεξάκης Χρήστος Α.; Παναγόπουλος Γιάννης; Σπηλιώτης Αριστοτέλης (SPOUDAI Journal of Economics and Business, 2000)
An issue which has attracted the attention of many monetarist economists is the relationship between public debt and the money stock. The question addressed in this paper is what theoretical and empirical basis is there for the beliefs that public sector deficits will result in an expansion of money supply. In our analysis we used the Lutkepohl and Reimers version of the Johansen cointegration approach in order to investigate the relationship between public deficit and money supply in the Greek economy. Our results give support to a strong relationship between the public deficit and the broad money supply (M3), suggesting that the Greek financial system was operating with a high degree of monetization for the period under examination. JEL Classification: E52, C50